2021
DOI: 10.3389/fimmu.2021.661202
|View full text |Cite
|
Sign up to set email alerts
|

Function of Protein S-Palmitoylation in Immunity and Immune-Related Diseases

Abstract: Protein S-palmitoylation is a covalent and reversible lipid modification that specifically targets cysteine residues within many eukaryotic proteins. In mammalian cells, the ubiquitous palmitoyltransferases (PATs) and serine hydrolases, including acyl protein thioesterases (APTs), catalyze the addition and removal of palmitate, respectively. The attachment of palmitoyl groups alters the membrane affinity of the substrate protein changing its subcellular localization, stability, and protein-protein interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 212 publications
(270 reference statements)
0
25
0
Order By: Relevance
“…Although changes in the global protein S-palmitoylation pattern have been associated with different physiological states such as cellular differentiation ( Zhang & Hang, 2017 ) and pathological conditions ( Zhang et al, 2021 ), the detailed molecular mechanisms of how protein S-palmitoylation regulates these processes remained to be defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although changes in the global protein S-palmitoylation pattern have been associated with different physiological states such as cellular differentiation ( Zhang & Hang, 2017 ) and pathological conditions ( Zhang et al, 2021 ), the detailed molecular mechanisms of how protein S-palmitoylation regulates these processes remained to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…Although changes in the global protein S-palmitoylation pattern have been associated with different physiological states such as cellular differentiation (Zhang & Hang, 2017) and pathological conditions (Zhang et al, 2021), the detailed molecular mechanisms of how protein S-palmitoylation regulates these processes remained to be defined. In an earlier study of protein S-palmitoylation in S. pombe, using the synchronized meiosis induced from pat1-114 diploid cells, Zhang et al (2013) demonstrated that the global protein S-palmitoylation pattern was significantly altered and shaped by varying Erf2 palmitoylacyltransferase activity during meiosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the last cysteine residue where palmitoylation occurs in T. gondii is not conserved across multiple members of the Plasmodium spp., including P. berghei [ 40 ]. Investigating whether this difference accounts for the lack of cross-species interaction is beyond the scope of this study, but given that cysteine palmitoylation has a profound effect on immune-related aspects [ 41 , 42 ], it would be an interesting area to study in the future. Interestingly, human sample antibody responses were substantially lower than those elicited by murine sera.…”
Section: Discussionmentioning
confidence: 99%
“…However, this approach has the defects of limited sensitivity and poor security. New technologies, such as acy-biotinyl exchange and click-chemistry that allow S-palmitoylation sites to be experimentally-determined have greatly promoted the study of this lipid modification ( 112 ). Currently, the research progresses of IFITM3 S-palmitoylation were listed in Table 1 .…”
Section: Mechanism Of S-palmitoylation To Regulate the Antiviral Capa...mentioning
confidence: 99%